تأثير رأس المال الفكري على تحقيق سلوكيات المواطنة التنظيمية في الجامعات الفلسطينية (جامعة الأزهر- غزة أنموذج) - الخطيب, محمد حسن; حكيم, بن حسان (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى الكشف عن تأثير رأس المال الفكري على تحقيق سلوكيات المواطنة التنظيمية في الجامعات الفلسطينية (جامعة الأزهر أنموذج)، واستخدمت الدراسة المنهج الوصفي التحليلي، وتكون مجتمع الدراسة جميع العمداء ومدراء الكليات ورؤساء الأقسام وأعضاء هيئة التدريس في جامعة الأزهر بغزة، فلسطين من العام 2017-2018م، والذي يبلغ عددهم (272) مبحوثاً، وقد طبقت استبانة مكونة من (34) فقرة متعلقة بالمتغير المستقل (رأس المال الفكري)، و(20) فقرة متعلقة بالمتغير التابع (سلوكيات المواطنة التنظيمية). وقد جاءت النتائج مؤكدة للفرضية الرئيسة القائلة: يوجد علاقة تأثير ذات دلالة إحصائية بين مختلف متطلبات رأس المال الفكري (البشرية، الهيكلية، العلائقية) في تحقيق سلوكيات المواطنة التنظيمية لدى العاملين في جامعة الأزهر إذ بلغ معامل الارتباط (71%)، وحجم تأثير قدره (56%). كما كشفت أنه لا توجد علاقة تأثير ذات دلالة إحصائية في متوسطات إجابات أفراد عينة الدراسة حول كل من متطلبات رأس المال الفكري على تحقيق سلوكيات المواطنة التنظيمية من وجهة نظر العاملين في جامعة الأزهر تعزى إلى المتغيرات (الجنس، المستوى الوظيفي، سنوات الخدمة). وقد قدمت الدراسة عدد من التوصيات التعامل مع رأس المال الفكري على أنه مورد رئيسي واستراتيجي من بين الموارد التي تمتلكها الجامعة، بناء ثقافة تنظيمية إيجابية حول رأس المال الفكري ونشرها وتعزيزها، من الضروري أن تتبنى الجامعة مناخ يسهم في تحسين التعاون بين العاملين والتكامل والثقة المتبادلة والتفاعل الإيجابي التي تدعم سلوك المواطنة التنظيمية، مع أهمية توفير أنظمة الحوافز والمكافآت للعاملين ضمن أبعاد سلوك المواطنة التنظيمية. The study was designed to reveal the influence of intellectual capital on the achievement of organizational behaviors in Palestinian universities (Al-Azhar University model). The study used the analytical descriptive method. The study community is composed of all deans, heads of departments and faculty members of Al-Azhar University in Gaza, (272) respondents. A questionnaire consisting of (34) paragraphs related to the independent variable (intellectual capital) and (20) related to the dependent variable (organizational behaviors) were applied. The results were confirmed by the main hypothesis: There is a statistically significant correlation between the different requirements of intellectual capital (human, structural, relational) in achieving the organizational behaviors of the employees of Al-Azhar University. Factor correlation of (71%) and Influence of (56%). It also revealed that there is no statistically significant correlation between the responses of the study sample members on each of the intellectual capital requirements on the achievement of organizational citizenship behaviors from the point of view of the employees of Al-Azhar University due to variables (gender, level of service, years of service). The study has made several recommendations to deal with intellectual capital as a major and strategic resource among the resources owned by the university. To build a positive organizational culture on intellectual capital and to disseminate and promote it, it is necessary for the university to adopt a climate that contributes to improving cooperation between employees, which supports the organizational behavior, with the importance of providing systems of incentives and rewards for employees within the dimensions of the organization.
مقال
Keywords: رأس المال الفكري - سلوكيات المواطنة التنظيمية - الجامعات الفلسطينية; Intellectual Capital - Organizational Behaviors - Palestinian Universities